Continuous biosorption of single and binary metal solutions in a fixed-bed column using algae Gelidium and granulated algal waste from agar extraction - Vítor Vilar (2008)
This paper describes the biosorption of single (Zn(II) and Cr(III)) and binary (Cd(II)/Zn(II) and Cu(II)/Cr(III)) metal solutions in a packed bed column using algae Gelidium and an algal waste from the agar extraction industry immobilized with polyacrylonitrile. In the sorption process, Zn(II) breaks through the column faster than Cd(II) due to its lower affinity for the biosorbent. An overshoot in the outlet Zn(II) concentration was observed and explained by competitive adsorption between Cd(II) and Zn(II), whereby the higher Cd(II) affinity for the biosorbent displaces bound Zn(II) ions. The same was verified for the binary system Cu(II)/Cr(III), where an overshoot in the outlet Cu(II) concentration also appeared. Metal desorption using 0.1 M HNO3 as eluant was 100% effective for Cd(II), Zn(II) and Cd(II)/Zn(II) systems. For Cr(III) and Cu(II)/Cr(III) systems, the elution of Cr(III) was not 100% effective. A mathematical model for a fixed-bed system considering film and intraparticle diffusion, equilibrium represented by single and binary Langmuir equations and desorption described by the mass action law, was developed. The uptake breakthrough and elution curves obtained in fixed-bed experiments were adequately predicted by the model.